2015
DOI: 10.1177/0300060515586246
|View full text |Cite
|
Sign up to set email alerts
|

Role of high sensitivity C-reactive protein and other risk factors in intracranial and extracranial artery occlusion in patients with ischaemic stroke

Abstract: Objective: A retrospective case-control study to identify stroke-associated risk factors and quantify serum C-reactive protein in patients with ischaemic stroke, with or without intracranial and/or extracranial artery occlusion (IEAO). Methods: Patients with ischaemic stroke and internal carotid artery occlusion (ICAO), middle cerebral artery occlusion (MCAO), ICAO þ MCAO, or no IEAO (control patients) were retrospectively recruited. Data regarding stroke-associated risk factors were retrieved from medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…30 C-reactive protein is a sensitive indicator of vascular inflammation and a marker of cerebral atherosclerosis. 31 In line with these previous results, the present study found that the plasma FGF23 concentration was positively correlated with that of C-reactive protein, with the latter also being higher in patients with accompanying ICAS than in those without cerebral atherosclerosis. Second, FGF23 is a phosphaturic hormone produced mainly by osteoblasts and osteocytes, and is implicated in blood calcium and phosphate concentrations, the vitamin D pathway, and ectopic site mineralization.…”
Section: Jcn Discussionsupporting
confidence: 92%
“…30 C-reactive protein is a sensitive indicator of vascular inflammation and a marker of cerebral atherosclerosis. 31 In line with these previous results, the present study found that the plasma FGF23 concentration was positively correlated with that of C-reactive protein, with the latter also being higher in patients with accompanying ICAS than in those without cerebral atherosclerosis. Second, FGF23 is a phosphaturic hormone produced mainly by osteoblasts and osteocytes, and is implicated in blood calcium and phosphate concentrations, the vitamin D pathway, and ectopic site mineralization.…”
Section: Jcn Discussionsupporting
confidence: 92%
“…This matches the results of other studies [87]- [89]. 2) Laboratory markers of stroke severity C-reactive protein (CRP) is a known marker of an early diagnosis of stroke, its recurrence and severity [90], [91].…”
Section: ) Stroke Severity and Background Diseasessupporting
confidence: 88%
“…Therefore, identification of biomarkers for atherosclerosis-artery stenosis or occlusion is essential for the early prevention of stroke. Considerable studies have already shown that an elevated serum CRP level reflects an increased tendency for plaque rupture and a high atherosclerotic burden [13,32,33,[40][41][42].…”
Section: Hscrp In the Prediction Of Atherosclerosis-artery Stenosis Or Occlusionmentioning
confidence: 99%
“…Although many inflammatory biomarkers have been reported to be useful in predicting clinical outcome after stroke, hsCRP remains one of the most widely used in clinical practice [8][9][10][11][12]. Increased hsCRP has been associated with the development of atherosclerosis, ischaemic attacks, hemorrhagic stroke, as well as disease outcomes [13][14][15][16][17]. Studies suggest that post-stroke inflammatory responses may exacerbate tissue damage after cerebral infarction and affect clinical outcomes [18,19].…”
Section: Introductionmentioning
confidence: 99%